2014
DOI: 10.1111/pace.12474
|View full text |Cite
|
Sign up to set email alerts
|

Improving Atrial Fibrillation Detection in Patients with Implantable Cardiac Devices by Means of a Remote Monitoring and Management Application

Abstract: The AFinder web-based software, applied on top of standard in-hospital and remote monitoring, improved AF detection and enabled OAC treatment to be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…For example, algorithms to optimize scanning of all transmissions to identify CIED patients with AF enhanced AF detection sensitivity by 10% and improved oral anticoagulation optimal treatment by 6%. 145 An AI tool to filter AF alerts resulted in an 84% reduction in notification workload, while preserving patient safety. 146 Interestingly, neural network modelling of remotely acquired device-based data helped to identify patients at risk of malignant ventricular arrhythmias and appropriate device therapies within 30 days.…”
Section: Transition To Digital Healthmentioning
confidence: 99%
“…For example, algorithms to optimize scanning of all transmissions to identify CIED patients with AF enhanced AF detection sensitivity by 10% and improved oral anticoagulation optimal treatment by 6%. 145 An AI tool to filter AF alerts resulted in an 84% reduction in notification workload, while preserving patient safety. 146 Interestingly, neural network modelling of remotely acquired device-based data helped to identify patients at risk of malignant ventricular arrhythmias and appropriate device therapies within 30 days.…”
Section: Transition To Digital Healthmentioning
confidence: 99%
“…La detección de FA silente por los DCEI nos ofrece la posibilidad de una intervención temprana, y varios estudios han demostrado la eficacia de la monitorización remota en el diagnóstico precoz de la FA y en el inicio temprano de la terapia anticoagulante en el caso de estar indicada 3 .…”
Section: ¿Cuándo Está Indicada La Anticoagulación?unclassified
“…A number of studies have recently demonstrated that RM reduces the total number of in-office visits, [4,6] without negative effects on patient outcome; [7,8] some studies have also shown the positive clinical impact of RM. [9][10][11][12] Although RM can reduce clinical staff time compared to standard in-office follow-up, [13][14][15] organizational workflow changes and a new definition of roles and responsibilities may be needed to review remote transmissions in an effective, efficient and timely manner. [16] Considering that most RM data does not require any clinical escalation, [1,14] it has been hypothesized that the remote triage may be outsourced and that this would optimize the time allocation of highly skilled healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%